An exploration into the quality of life of women treated for cervical cancer at an academic hospital in Gauteng, South Africa - Sabulei, Caroline (My University, 2017)
Quality of life is a multidimensional, subjective and individualized concept influenced by culture and value systems. Cancer as a disease remains a major health problem globally and it’s estimated that 528 000 women are diagnosed with cervical cancer annually whilst 266 000 will die each year. In Africa cervical cancer statistics indicate that there are 99 038 incidences and 60,098 cervical cancer related deaths (International Agency for Research in Cancer and World Health Organization, 2012). Women with cervical cancer experience physical, psychological and sex-related problems as the consequences of both the disease and treatment and this affects their quality of life. Research Question: What is the quality of life of women treated for cervical cancer at an academic hospital in Gauteng? Purpose of the study was to explore the quality of life in cervical cancer during treatment, at six months and twelve months post treatment at an academic hospital in Gauteng. Aims of the study: The objectives of the study were (1) to explore the quality of life in cervical cancer patients treated with radiation therapy and (2) to compare with the quality of life of women at six months and twelve months after completion of treatment at an academic hospital in Gauteng. Research Design: This is a cross sectional and explorative study. A sample of 153 women was recruited using a convenience sampling for the three groups and data were collected using the EORTC QLQ-C30 and QLQ-CX24 questionnaires. The data were captured on an excel spreadsheet and analysed using SPSS IBM 22.0. Results: The overall quality of life of the respondents was affected by the acute side effects experienced during treatment. Cancer related symptoms improved with radiotherapy treatment. Physical functioning was reported as the most affected domain while social functioning was the least affected.
A research report submitted to the Faculty of Health Science, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirement for the degree of Master of Science in Nursing Johannesburg, 2017
Keywords: Cervical Cancer Quality of Life